A Systematic Approach to Diagnosing Arthritis Based on Radiological Imaging - Lee, Kyu-Chong; Ahn, Kyung-Sik; Kang, Chang H.; Hong, Suk Joo; Kim, Baek Hyun; Shim, Euddeum (Current Medical Imaging, 2022)
Radiology plays a key role in the diagnosis of arthritis. We herein suggest an algorithmic approach to diagnosing arthritis. First, the number of joint involvements is reviewed. Monoarticular arthritis includes septic arthritis, pigmented villonodular synovitis, and synovial chondromatosis. Second, polyarticular arthritis can be categorized by its characteristics: erosive, productive, and mixed. Erosive disease includes rheumatoid arthritis, hemophilia, and amyloidosis, while productive disease includes osteoarthritis and hemochromatosis. Third, mixed diseases are subcategorized by symmetricity. Ankylosing spondylitis and inflammatory bowel disease related arthritis affect joints symmetrically, while psoriatic arthritis, reactive arthritis, and crystalline arthropathy are asymmetric. Adjacent soft tissue density, periostitis, and bone density are ancillary findings that can be used as additional differential diagnostic clues. The final step in identifying the type of arthritis is to check whether the location is a site frequently affected by one particular disease over another. This systematic approach would be helpful for radiologists in diagnosing arthritis.
Keywords: Pigmented villonodular synovitis